YUCCA-Mediated Biosynthesis of the Auxin IAA Is Required during the Somatic Embryogenic Induction Process in Coffea canephora - Uc-Chuc, Miguel A. (Int J Mol Sci, 2020)
Despite the existence of considerable research on somatic embryogenesis (SE), the molecular mechanism that regulates the biosynthesis of auxins during the SE induction process remains unknown. Indole-3-acetic acid (IAA) is an auxin that is synthesized in plants through five pathways. The biosynthetic pathway most frequently used in this synthesis is the conversion of tryptophan to indol-3-pyruvic acid (IPA) by tryptophan aminotransferase of Arabidopsis (TAA) followed by the conversion of IPA to IAA by enzymes encoded by YUCCA (YUC) genes of the flavin monooxygenase family; however, it is unclear whether YUC-mediated IAA biosynthesis is involved in SE induction. In this study, we report that the increase of IAA observed during SE pre-treatment (plants in MS medium supplemented with 1-naphthaleneacetic acid (NAA) 0.54 µM and kinetin (Kin) 2.32 µM for 14 days) was due to its de novo biosynthesis. By qRT-PCR, we demonstrated that YUC gene expression was consistent with the free IAA signal found in the explants during the induction of SE. In addition, the use of yucasin to inhibit the activity of YUC enzymes reduced the signal of free IAA in the leaf explants and dramatically decreased the induction of SE. The exogenous addition of IAA restored the SE process in explants treated with yucasin. Our findings suggest that the biosynthesis and localization of IAA play an essential role during the induction process of SE in Coffea canephora.